Advances in management accounting - Akroyd, Chris (Associate professor of accounting); Burney, Laurie L. (Advances in management accounting, 2021)
Advances in Management Accountingis a publication of quality applied research in management accounting. The journal's purpose is to publish thought-provoking articles that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners.